Occurrence of the tick Ixodes ricinus (L.) under the conditions of anthropopressure - Daniel, M; Cerný, V (Folia parasitologica, 1990)
The authors report on their findings of the tick Ixodes ricinus under urban conditions of Prague. The concrete data were taken as a basis for a general scheme of possible occurrence of this species in various town parts, determined by the state of vegetation and presence of large mammals. Discussed are also conditions for I. ricinus maintenance in another type of anthropogenous landscape, the spoil banks resulting from brown coal exploitation.
Keywords: arachnida jako vektory; Urban Health; Ticks; Československo; Animals; zdraví ve městech; klíšťata; zvířata; Arachnid Vectors; Czechoslovakia